Lost. The complete third season. The unexplored experience [videorecording (DVD)] - Fox, Matthew, 1966-; Lilly, Evangeline, 1979-; Monaghan, Dominic, 1976-; Garcia, Jorge, 1973-; Andrews, Naveen, 1969- (Distributed by Buena Vista Home Entertainment, 2007)
As the power of the island to both heal and destroy comes into sharp focus, the lines between good and evil are blurred and loyalties are challenged when the survivors of the crash become tangled within the lives of the Others.